PEMETAAN SOFT SKILLS GURU TAMAN KANAK-KANAK DI KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Mar’atun Sholeha Sholeha; Zulkifli N '; Devi Risma Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to mapping the soft skills of kindergarten teachers at Payung Sekaki District of Pekanbaru City. The population in this research were 123 teachers. The sample in this study was determined by using the formula of Slovin which totaled 94 teachers. The techniques of data collection used is to using a written test and analysis techniques used is using a percentage formula. The results of this research obtaining of the mapping of kindergarten teacher’s soft skills at Payung Sekaki District for  personal competence aspects  which is in the category of "Very Good". It is known from the results of the data analysis of soft skills which earn a percentage of 82.76%. While the mapping of  kindergarten teacher’s soft skills at Payung Sekaki District for social competence aspects which  is in the category of "Very Good". It is known from the results of the data analysis which earn a percentage of 88.52%. The mapping of kindergarten teachers’s soft skills at Payung Sekaki district overall earn a percentage of 84.48%, which can be classified in the category of "Very Good". Keyword: Soft Skills, Teacher.